2020
DOI: 10.1101/2020.08.11.246850
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Beneficial effects of cerebellar tDCS on motor learning are associated with altered putamen-cerebellar connectivity: a simultaneous tDCS-fMRI study

Abstract: Non-invasive transcranial stimulation of cerebellum and primary motor cortex (M1) has been shown to enhance motor learning. However, the mechanisms by which stimulation improves learning remain largely unknown. Here, we sought to shed light on the neural correlates of transcranial direct current stimulation (tDCS) during motor learning by simultaneously recording functional magnetic resonance imaging (fMRI). We found that right cerebellar tDCS, but not left M1 tDCS, led to enhanced sequence learning in the ser… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 66 publications
2
2
0
Order By: Relevance
“…However, subjects of both groups made significantly more errors during random (RND) compared to sequence (SEQ) blocks. This effect is consistent with our previous findings in MSL tasks in healthy young subjects, in which larger error-rates in RND compared to SEQ blocks were found (Liebrand et al, 2020; Tzvi et al, 2016, 2015). Previously, we interpreted this effect as an implicit attempt to perform the sequence or chunks of the sequence in RND trials following sequence learning, however unsuccessfully.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, subjects of both groups made significantly more errors during random (RND) compared to sequence (SEQ) blocks. This effect is consistent with our previous findings in MSL tasks in healthy young subjects, in which larger error-rates in RND compared to SEQ blocks were found (Liebrand et al, 2020; Tzvi et al, 2016, 2015). Previously, we interpreted this effect as an implicit attempt to perform the sequence or chunks of the sequence in RND trials following sequence learning, however unsuccessfully.…”
Section: Discussionsupporting
confidence: 93%
“…We expected to find evidence for abnormal striatal activity in PD reflected in connections with putamen. Using Bayesian model selection, we found that in the optimal model in both pwPD and controls connections from M1 and premotor areas to cerebellum were modulated by the motor task, replicating our previous findings (Liebrand et al, 2020; Tzvi et al, 2017, 2015, 2014). Importantly, we found no evidence for differences in modulatory parameters between PD and controls.…”
Section: Discussionsupporting
confidence: 86%
“…However, besides local plasticity, online and offline stages of motor sequence learning rely on the dynamic recruitment of nodes of a distributed motor learning network that includes M1, the premotor cortex, the supplementary motor area, the cerebellum, basal ganglia, the hippocampus, and parietal cortical areas [ 40 45 ]. A recent fMRI study showed that alterations of sequence-specific motor learning in young healthy subjects induced by cerebellar tDCS were related to altered activity in M1, the cerebellum, the inferior frontal gyrus, and the right parietal lobule [ 46 ] suggesting that tDCS facilitated motor sequence learning by alterations of long-range network communication. Long-range network connectivity may be compromised in pwMS by both disease-related white matter lesions and affection of grey matter [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…To induce plasticity, we used procedures previously described to be effective in inducing plasticity in the cerebellum. In experiment 1, 1 Hz rTMS 50 , PAS 17 , cTBS 44,51 , and anodal tDCS [64][65][66] was used. 1 Hz rTMS was administered with 90% RMT for 20 min using a Magstim Rapid magnetic stimulator (Magstim Company, Whitland, Dyfed, UK) 50 .…”
Section: Transcranial Magnetic Stimulation Single-and Multi-pulse Tmmentioning
confidence: 99%